Pengaruh Penggunaan Media Berbantu Aplikasi Canva terhadap Kemampuan Literasi Siswa Sekolah Dasar - Yuliana, Wiji; Purmadi, Ary (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Elementary school students' literacy skills remain a challenge that requires serious attention. Observations at SD Negeri 2 Karya Jaya, Ogan Komering Ilir, on November 3, 2025, showed that some students experienced difficulties in reading comprehension and writing, characterized by limitations in understanding reading content, constructing coherent sentences, and expressing ideas in writing. This condition is influenced by a lack of engaging reading materials, suboptimal literacy culture, inadequate parental guidance at home, and high use of gadgets for gaming. This study aims to determine the effect of using the Canva application-based learning media on elementary school students' literacy skills. The research method used was quantitative research with an experimental design. The results showed that the use of the Canva application had an impact on students' literacy skills. The conclusion of this study indicates that the use of the Canva application is effective in improving students' literacy skills at SD Negeri 2 Karya Jaya.